1995
DOI: 10.1152/ajpheart.1995.269.5.h1827
|View full text |Cite
|
Sign up to set email alerts
|

VEGF gene expression is upregulated in electrically stimulated rat skeletal muscle

Abstract: Vascular endothelial growth factor (VEGF; also called vascular permeability factor) is a secreted mitogen with distinct target cell specificity for vascular endothelial cells. Hypoxia upregulates VEGF expression, making it a likely mediator of the angiogenesis that occurs in poorly perfused tissues. The purpose of this study was to determine whether VEGF gene expression is upregulated in chronically stimulated skeletal muscles, where hypoxia is thought to trigger the growth of blood vessels. The right anterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
115
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(122 citation statements)
references
References 0 publications
6
115
1
Order By: Relevance
“…Evidence exists that electrical stimulation (ES) increases the release of VEGF in the muscle and wound site [7][8][9][10][11][12]. Thus, recruitment of muscle by ES may be a way to facilitate angiogenesis in wound healing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence exists that electrical stimulation (ES) increases the release of VEGF in the muscle and wound site [7][8][9][10][11][12]. Thus, recruitment of muscle by ES may be a way to facilitate angiogenesis in wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, recruitment of muscle by ES may be a way to facilitate angiogenesis in wound healing. Hang et al reported the VEGF gene expression is unregulated in rat skeletal muscle [7]. They stimulated muscle electrically at 10 Hz using 300 ms square waves at voltages that maximized contraction on palpation for up to 21 days.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, electrical stimulation increases VEGF levels [10]. Recently, it was demonstrated that passively-induced hyperperfusion does not increase muscle VEGF mRNA, and it was speculated that either intracellular hypoxia or mechanical effects of contraction per se (such as ®bre stretch) may be responsible for this increase [11].…”
mentioning
confidence: 99%